Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/ja902054w
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Phase Transition in Solution-Grown VO2 Nanostructures

Abstract: The first-order metal-insulator phase transition in VO(2) is characterized by an ultrafast several-orders-of-magnitude change in electrical conductivity and optical transmittance, which makes this material an attractive candidate for the fabrication of optical limiting elements, thermochromic coatings, and Mott field-effect transistors. Here, we demonstrate that the phase-transition temperature and hysteresis can be tuned by scaling VO(2) to nanoscale dimensions. A simple hydrothermal protocol yields anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
184
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(205 citation statements)
references
References 52 publications
16
184
0
Order By: Relevance
“…56 The incorporation of VO 2 in polymer matrices 57,58 has been demonstrated too. Nanoparticles of VO 2 with more or less symmetrical shapes have been made by wet chemistry, [59][60][61][62][63][64][65][66] 74 There are also numerous works on nanorods ͑nanowires͒ of VO 2 prepared by wet chemistry, [75][76][77][78][79][80][81][82] gas phase synthesis, 32,[83][84][85][86][87][88][89] ion implantation of vanadium and oxygen ions followed by annealing, [27][28][29]90 and by thermal oxidation of V; 33,91 these particles can be represented as higheccentricity prolate particles. VO 2 : W nanorods have been deposited by wet chemistry 92 and VO 2 : Mo nanorods have been made by a sol-gel based technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The incorporation of VO 2 in polymer matrices 57,58 has been demonstrated too. Nanoparticles of VO 2 with more or less symmetrical shapes have been made by wet chemistry, [59][60][61][62][63][64][65][66] 74 There are also numerous works on nanorods ͑nanowires͒ of VO 2 prepared by wet chemistry, [75][76][77][78][79][80][81][82] gas phase synthesis, 32,[83][84][85][86][87][88][89] ion implantation of vanadium and oxygen ions followed by annealing, [27][28][29]90 and by thermal oxidation of V; 33,91 these particles can be represented as higheccentricity prolate particles. VO 2 : W nanorods have been deposited by wet chemistry 92 and VO 2 : Mo nanorods have been made by a sol-gel based technique.…”
Section: Discussionmentioning
confidence: 99%
“…[125][126][127] There is a tendency that limited dimensions decreases c and widens the hysteresis in nanocrystalline films 46,48,[128][129][130][131][132][133][134][135] and nanorods. 27,28,81,90,118 This may be associated with internal stress in the particles. However, the empirical data are not entirely consistent and we prefer not to discuss the differences between particles and thin films in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many research groups have invested massive efforts not only to identify the origin of the phase transition in VO2, but also to control the occurrence of the phase transition onset by varying many physical parameters, such as doping, [15,16] strain, [17,18] pulsed voltage, [19,20] and size, [21][22][23] . [15,16] Recently, Whittaker et al reported that the phase transition temperature can be decreased by oxygen vacancy doping, which is induced by reducing VO2 crystal size to nanoscale.…”
mentioning
confidence: 99%
“…[15,16] Recently, Whittaker et al reported that the phase transition temperature can be decreased by oxygen vacancy doping, which is induced by reducing VO2 crystal size to nanoscale. [22] Variations of crystal dimensions also provide a way to control the onset of the phase transition in VO2.…”
mentioning
confidence: 99%
“…With the continuous research of vanadium dioxide in recent years, the control technology of vanadium dioxide phase transition temperature has been basically mature, mainly in the following three ways: adjust the applied stress [8][9], control the microstructure [10][11][12] and ion doping [13][14][15]. But the control of the phase change field strength was basically not studied, There were two main reasons for this.…”
Section: Introductionmentioning
confidence: 99%